MON-178 Cyclical Cushing’s Syndrome in 12 Patients with Ectopic ACTH Secretion - Zenno, Anna (J Endocr Soc, 2020)
Background: Cyclical Cushing’s syndrome (CCS) is characterized by alternating periods of endogenous hypercortisolism and eucortisolism. A literature survey of 60 adult patients with CCS found 15 to have ectopic ACTH secretion (EAS) (1). The duration and frequency of hypercortisolemia are unpredictable, creating a diagnostic challenge. Objective: Describe biochemical and clinical characteristics of patients with CCS due to occult or histologically proven ectopic ACTH-secreting neuroendocrine tumor (NET). Methods: We conducted a retrospective medical record review of 12 adults with EAS admitted to our institution. Inclusion required 1) evidence of ectopic ACTH tumor from biochemical testing (CRH stimulation, 8 mg dexamethasone suppression [DST], and/or inferior petrosal sinus sampling [IPSS]) or pathology results and 2) cycles of hypercortisolism (Hi-F) to eucortisolism (Eu-F) off medical treatment. Results: Average age on admission was 61 (46-79) years; 58% were women. All 12 had biochemical evidence of ACTH-dependent Hi-F. IPSS results suggested EAS in 9 patients, 8 of whom had Hi-F for more than two months, and 1 whose cycles occurred every 5 - 7 days. IPSS was consistent with Cushing’s disease (CD) in 2 patients after Hi-F of only 6 -7 weeks and one with Eu-F on admission, estimated duration < 4 weeks. DST suggested EAS in 9 patients, and CD in the one with recent Eu-F. CRH was consistent with EAS in 10 patients, but suggested CD in 2 with marginal increases in ACTH (34.5%, 38%) but not cortisol. 7 patients had ACTH-secreting tumor on pathology (5 pulmonary, 1 pancreas, 1 appendix NET), and 5 had occult presumed EAS. Time from one Hi-F episode to the next ranged from 1 week to 6 years with Hi-F duration of 3 days to 5 years. 24-hour urine free cortisol (UFC) levels were 17 - 301 times the upper reference range (RR) during Hi-F periods. During Eu-F, lowest UFCs were within RR in 9 patients and subnormal in 3. Hypokalemia occurred in 11 patients with Hi-F; increasing values paralleled movement to Eu-F. Conclusion: Patients with possible ectopic ACTH-secretion and CCS may pose a diagnostic challenge: clinical and biochemical evidence of hypercortisolemia may not be present, depending on the timing and/or duration of hypercortisolism. Furthermore, test results may inappropriately suggest Cushing’s disease if performed after less than 8 weeks of hypercortisolism, or with recent eucortisolism. Thus, weekly UFC measurement may facilitate diagnosis of cyclical Cushing’s syndrome and determine appropriate timing of dynamic testing such as inferior petrosal sinus sampling. Potassium may be a useful marker to determine when medical treatment can be tapered or stopped. 1. Meinardi JR, et al. Eur J Endocrinol. 157:245, 2007.